Formation of Foster Children's Morals Through A Coaching Program at The Orphanage of the Putera Harapan Muhammadiyah Children's Social Welfare Institution - Supala; Wasito (Yayasan Mentari Madani, 2024)
An orphanage is a social institution that is a place for children who need education, affection, attention and example. Because basically the orphanage is a place to prosper orphans, orphans, the poor, and so on. According to the information obtained, there are several problems that occur in foster children such as undiscipline, rude words, disrespectfulness, and disrespect for coaches. This is the background of researchers in the Formation of Foster Children's Morals through Coaching Programs in Orphanages. The implementation of good moral formation follows the pattern of orphanage education. and the overwhelming evidence of orphanage alumni who have an important role in society. The purpose of the orphanage is to mold people so that they are not abandoned and have proper education and have no attention to their families. This study aims to determine the moral formation program of foster children, the implementation of the foster child moral development program, supporting factors (internal and external) and inhibiting factors (internal and external), as well as the impact that occurs in the formation of foster children's morals through moral development programs in orphanages. The method used in this study is descriptive analysis with a qualitative approach related to the method. The data collection method is through interviews, observations, and documentation studies, with triangulation analysis techniques. The results showed that the moral formation program has a fairly good impact in improving noble morals, this is shown by improving: 1). discipline, 2). honesty